Maternal and child nutrition in Nepal: Examining drivers of progress from the mid-1990s to 2010s - Cunningham, Kenda; Headey, Derek D.; Singh, Akriti; Karmacharya, Chandni; Rana, Pooja Pandey (Elsevier, 2017)
This paper explores the drivers of Nepal's maternal and child nutrition success using document review, interviews with mothers, and quantitative analysis of DHS datasets. Our qualitative and quantitative analyses both highlight similar policy and community level changes but limited improvements in child feeding and care practices. Improvements in four key drivers of nutritional change emerged: health services, sanitation, education, and wealth. However, the relative contributions of each factor varied by indicator, with health services more important for linear growth among children, and sanitation more important for weight gain among both children and mothers. We conclude with a discussion bringing the qualitative and quantitative findings together into key lessons from Nepal's success.